Perencanaan Pembangunan Kawasan Agropolitan Kabupaten Sumenep - Mohammad Zainul Arief (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
The Agropolitan Area of ??Rubaru District, Sumenep Regency has enormous potentials especially the red onion of the Rubaru variety. Agro-industry, is an activity that can guarantee the optimal utilization of agricultural products by providing high added value through efforts to utilize, develop, master technology and biotechnology. As one of the sub-systems in agrobisnis, agro- industry has the great potential to drive economic growth, increasing people's incomes, absorb labor, and increas the distribution of development and its results and accelerate regional development. Adequate infrastructure and facilities in an area will be able to support the regional economy and will certainly increase the standard of living of the community. The adequate infrastructure and facilities in an area will be able to support the regional economy and will certainly increasing the standard of living of the community. The objective to be carried out is to realize that the development and Agropolitan Area can run well with the existence of detail cost calculated and technical drawings based on regional technical planning principles. The method used is descriptive quantitative. This planning can be used as a reference in carrying out physical/construction activities in the field in order to obtain efficiency and effectiveness and reliable buildings.